2006
DOI: 10.1007/s10592-006-9197-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of prey DNA in pinniped faeces: potential to estimate diet composition?

Abstract: We investigate using relative amounts of prey DNA recovered from pinniped faeces to obtain diet composition data. Faeces were obtained from captive sea lions being fed a diet containing three fish species (50%, 36% and 14% by mass). Real-time PCR was used to quantify mtDNA in undigested tissue and in the faecal samples. The percent composition of fish mtDNA extracted from tissue corresponded reasonably well to the mass of fish in the mixture. In faecal samples the absolute amount of fish mtDNA recovered varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 13 publications
9
132
0
1
Order By: Relevance
“…There is currently no precise way to quantify prey in the stomach using metabarcoding. Unfortunately, it cannot be assumed that the number of sequences for each particular species represents the amount of DNA (or number of individuals) contributing to the sample because the quality of that DNA depends on many factors including degradation and digestion rates (Deagle & Tollit 2007, Troedsson et al 2009, Valentini et al 2009b). Thus, quantitative analyses at this time are limited to the frequency of prey occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently no precise way to quantify prey in the stomach using metabarcoding. Unfortunately, it cannot be assumed that the number of sequences for each particular species represents the amount of DNA (or number of individuals) contributing to the sample because the quality of that DNA depends on many factors including degradation and digestion rates (Deagle & Tollit 2007, Troedsson et al 2009, Valentini et al 2009b). Thus, quantitative analyses at this time are limited to the frequency of prey occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Results are limited or biased to the frequency of occurrence, which still provides useful information when seeking to understand localized effects of an invasive predator. However, the underlying variability in DNA quality, differential breakdown of that DNA during digestion, and differences in digestion stages (Deagle & Tollit 2007, Troedsson et al 2009, Valentini et al 2009b, as well as the objective of identifying several different organisms within the same sample (i.e. the gut) (Valentini et al 2009a), still hinder the quantification aspect in metabarcoding of gut contents.…”
Section: Introductionmentioning
confidence: 99%
“…Direct quantification of prey consumption using amplicon numbers is not recommended because of potential differences in digestibility, individual size and amounts of mitochondrial DNA per gram of tissues from different prey species (Deagle et al, 2010). A few studies have shown that the proportion of prey species' DNA retrieved from predator faecal samples and amplified by qPCR can be somewhat representative of the proportion of biomass eaten (Deagle & Tollit, 2007;Bowles et al, 2011). And these sequence counts have been used as semiquantitative measures of the biomass of prey eaten (Deagle et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…One issue with their proposed method is that large quantities of DNA from one live specimen accidentally taken in one of their 0.5 kg soil cores could dominate the PCR process (Deagle & Tollit, 2007) and mask the presence of other species, or at least result in a biased representation of species abundance. Such bias could be minimised by collecting several small soil cores and mixing them together to make a more representative sample (Taberlet et al, 2012).…”
Section: Boxes Tables and Ifguresmentioning
confidence: 99%
“…2008a,b). Given the vast distances that lactating New Zealand fur seals travel to forage, interpreting diet using traditional methods is unlikely to accurately represent the diet of seals foraging in distant oceanic waters, or provide a means by which to detect and quantify the spatial separation of foraging habitats.Owing to such shortcomings, biochemical and molecular methods are increasingly being used to complement traditional methods in validating and/or providing information on dietary preferences of marine mammals (Iverson et al 1997, Cherel et al 2000, Deagle & Tollit 2007. One such technique is fatty acid (FA) analysis.…”
mentioning
confidence: 99%